Santripreneur: A Model of Islamic Economic Management Through Pesantren-Based Entrepreneurship Education - Akhmad Fauzi Hamzah (Al-Jadwa: Jurnal Studi Islam, 2026)
Islamic boarding schools (pesantren) in Indonesia are transforming, not only as centers of religious education but also as agents of economic empowerment through the development of entrepreneurship based on Islamic values. This study aims to analyze the strategies for forming santripreneur character, the transformation of students’ entrepreneurial spirit, and the empowerment model in managing business units at Pesantren Al Ma’ruf Kediri. Using a qualitative method with a case study approach, data were collected through participatory observation in business units (laundry, culinary, fisheries, etc.), in-depth interviews with caregivers, teachers (ustadz), and students (santri), as well as document analysis. The findings reveal that entrepreneurship education at this pesantren is holistically integrated through formal learning, seminars, study circles (halaqah), mentoring, and direct practice (experiential learning). This strategy effectively instills pesantren values such as independence, sincerity, honesty, and work ethic as a spiritual foundation in business, while simultaneously avoiding usury (riba) and exploitation. The empowerment model, based on structured mentoring and a task rotation system, successfully enhances the students’ entrepreneurial self-efficacy, fosters leadership qualities, and promotes the pesantren’s economic independence. In conclusion, the pesantren is capable of producing a generation of santripreneurs who are pious, morally upright, financially independent, and serve as agents of Islamic economic change adaptable to global dynamics.